Le genre à l'école maternelle : les représentations, jugements et attentes des enseignantes de grande section - Annette Jarlégan; Youssef Tazouti (Presses universitaires de la Méditerranée, 2012)
Since the 90s, many education research questioned the role of schools in the socialization of boys and girls and in the construction of gender differences. Some of these studies have focused on perceptions of teachers and their effects on scholastic judgments and teacher's expectations. This work has mainly been conducted in elementary school or college. We know so little about this issue in kindergarten. This article aims to examine how these representations, judgments and expectations contribute to the construction of gender as early as kindergarten. From a survey of 18 class, we analyze different types of judgments of teachers to determine whether the sex of the student is an element which underpins the teacher(s) when asked to judge their students. The collected data were analyzed using multivariate regression analysis.